ANALISIS HARGA SAHAM PADA PERUSAHAAN SEKTOR TEKNOLOGI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Demas Nugraha Hidayat (2022)
This research can be included in quantitative research where this study aims to determine the effect of the profitability variable and leverage on the stock price variable. This study uses the object of research, namely technology companies listed on the Indonesia Stock Exchange, this study uses a purposive sampling method which produces 12 companies during the 2017-2020 period as samples. The study was tested with a significance level of 5% using the Panel Data Regression Analysis Method with the help of a computer program, namely E-Views 12. Analysis of the influence of the x variable on y in this study resulted in the following results; (1) there is a significant effect between profitability on stock prices, (2) there is no significant effect between leverage on stock prices. Keywords: Profitability, Leverage, Stock Price